Circumferential trabecular meshwork cell density in the human eye. (April 2021) - Kuehn, Markus H.; Vranka, Janice A.; Wadkins, David; Jackson, Thomas; Cheng, Lin; Ledolter, Johannes
Abstract: The cells residing in the trabecular meshwork (TM) fulfill important roles in the maintenance of the tissue and the regulation of intraocular pressure (IOP). Here we examine (i) TM cell distribution along the circumference of the human eye, (ii) differences in TM cell density between regions of high and low outflow, and (iii) whether TM cell distribution in eyes from donors with primary open angle glaucoma (POAG) differs from that of normal eyes. Toward this end, the TM cell density from 12 radial segments around the circumference of the TM of human donor eyes (n = 6) with and without POAG was determined using histochemical methods. Areas of high, median, and low outflow were mapped in a different set of human donor eyes that were perfused in organ culture, and TM cell densities in these areas were determined in normal (n = 11) and POAG eyes (n = 6). Our analysis of 1380 tissue sections taken from the first set of six eyes shows that the average TM cell density of these six eyes ranges from 15.5 to 23.7 cells/100 μm and is negatively correlated to the maximum IOP recorded for each donor eye (R 2  = 0.91). Considerable differences in TM cell density exist among sections taken from the same segment of an individual eye (average standard deviation = 2.35 cells/100 μm). Less variability is observed among the segment averages across the eye's circumference (average standard deviation = 1.03 cells/100 μm). Variations in cell density are similar between normal and POAG eyes and are not correlated with the anatomic position of examined segments (p = 0.745). The analysis of the second set of eyes shows that TM regions of high outflow display a TM cell density similar to regions of median or low outflow in both normal and POAG eyes. Together these findings demonstrate that (i) statistically significant differences in TM cell density exist along the circumference of each eye (ii) TM cellularity is not correlated with segmental flow and (iii) eyes with POAG, while displaying reduced TM cellularity, do not exhibit higher TM cell variability than normal eyes. Finally, statistical analysis of sections and segments indicates that measurements from 12 sections taken from 2 segments provide a reliable and cost-effective estimate of a human eye's TM cell density. Highlights: We analyzed the circumferential density of trabecular meshwork cells in human eyes. TM regions of high or low aqueous humor outflow exhibit similar cell densities. The location of areas of relative high and low TM cell density are not conserved among eyes. Eyes with POAG exhibit similar variability in cell density than control eyes.